2012
DOI: 10.1111/j.1745-4549.2012.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Rheological, Sensorial and Functional Properties of Gelatinized Corn- Rice Bran Flour Composite Corn Flakes and Tortilla Chips

Abstract: In the present research, stabilized rice bran (SRB) of an Egyptian variety was used for the preparation of corn flakes and tortilla chips with and without fortification with rich protein sources. SRB was used as 10, 20 and 30% replacements of gelatinized corn flour. Doughs of different blends were evaluated rheologically. Color quality, sensory parameters and proximate composition of the products were assessed. Results showed that the maximum and breakdown viscosity and color quality was affected by the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…The obtained results are also was higher than those obtained by Al-Okbi et al (2014) who found that the b- carotene of whole rice bran extracted by hexane was 101.0 lg/100 g. Zhou et al (2004) suggested that bran samples might significantly differ in their carotenoid profiles due to the wheat variety and growing condition. Panfili et al (2004) reported that wheat germ contained total carotenoids about 5.5 lg/g.…”
Section: Carotenoidscontrasting
confidence: 64%
“…The obtained results are also was higher than those obtained by Al-Okbi et al (2014) who found that the b- carotene of whole rice bran extracted by hexane was 101.0 lg/100 g. Zhou et al (2004) suggested that bran samples might significantly differ in their carotenoid profiles due to the wheat variety and growing condition. Panfili et al (2004) reported that wheat germ contained total carotenoids about 5.5 lg/g.…”
Section: Carotenoidscontrasting
confidence: 64%
“…Related studies found that replacing 10% of fat content of frankfurters with a total fat content of 30% (control) with rice bran fiber and vegetable oils did not affect the sensory properties of the frankfurters . Supplementation of corn flour with rice bran flour seems to improve the organoleptic properties of corn flakes and tortilla chips …”
Section: Rice Bransmentioning
confidence: 97%
“…Bran is obtained by de‐branning or polishing process and constitutes 5–10% of brown rice. It is mainly composed of protein, fiber, oil, vitamins, minerals, and starch derived from endosperm during polishing (Al‐Okbi, Hussein, Hamed, Mohamed, & Helal, ). It is also a good source of antioxidants such as polyphenols, tocopherols, tocotrienols, and γ‐oryzanol which help in preventing oxidative damage of body tissues and DNA.…”
Section: Introductionmentioning
confidence: 99%